Pre-clinical experiences among nursing students of reputable Islamic university in the capital city of Indonesia - Jamaludin, Jamaludin; Rahmanda, Mutiara Eka; Rahman, Handono Fatkhur (Intelektual Pustaka Media Utama, 2024)
Clinical trainings were employed in the nursing sciences in order to provide student’s experiences in applying nursing care according to the theory. They required to accomplish some competencies depending on their study levels. Students would also experience the possible barriers and challenge during clinical trainings. However, there were limited number of research which explored these experiences, especially in nursing students. This study aimed to explore the experiences of nursing students in performing fundamental nursing pre-clinical activities. This research conducted qualitative study with phenomenological approach. This study involved 5 nursing students according to inclusive criteria. Data collection method used in-depth interview techniques. The obtained data were analysed further using Colaizzi test. The collected data identified six themes of student’s experiences, such as student’s understanding about pre-clinic, their experiences during preclinic, theoretical gaps with hospital procedures, some barriers in clinical practice, student’s expectation, and obtained support during pre-clinic trainings. Pre-clinical trainings allowed nursing students to gain various medical experience and knowledge regarding nursing care. They could implement and compare the nursing theory with actual conditions in the hospital and society living. This topic needed to assess further about the benefits of pre-clinic trainings.